Education and austerity in the European Union from an autism perspective: Policy mapping in Ireland, Portugal, Italy, and Greece - van Kessel, R. (2021)
This study explores how autism and education policy are affected by austerity measures in Ireland, Portugal, Italy, and Greece by using a path dependence analysis. The implementation of mixed mainstream classrooms and improvements to infrastructure coincided with the ratification of inclusive education policy. Austerity measures appeared temporally associated with furthering of integration and inclusion policy for all countries under study, potentially due to the economic incentives of an integrated system. This trend is especially visible in Ireland, Portugal, and Greece, whereas lesser so in Italy. Even though the initial focus of this analysis was autism, the findings are applicable to the general area of special education needs due to the non-specific nature of national policies.